Georgia Architectural and Historic Properties Survey of Rural [239] Southern/west section of the countyv Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [239] South western section of county, Valdosta, Ga. December 1980. A one story rectangular plan with gabled roof and clapboard siding. Screened porch with carved posts. Exterior chimney, brick piers. Good condition. Date of construction: c. 1920. A typical rural farmhouse common to this area.
Georgia Architectural and Historic Properties Survey of Rural [239] South western section of county, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 80.7 MB (84,657,292 bytes).
Keywords: Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)